2008
DOI: 10.1038/gene.2008.34
|View full text |Cite
|
Sign up to set email alerts
|

Duplication, mutation and recombination of the human orphan gene KIR2DS3 contribute to the diversity of KIR haplotypes

Abstract: The KIR2DS3 gene is an activating homologue of the inhibitory killer-cell immunoglobulin-like receptors (KIR) that recognize HLA-C molecules, enabling NK cells to survey the normal function of endogenous antigen presentation. The genetics of KIR2DS3 is complicated by the existence of alleles with similar coding sequences that map to different regions of the KIR complex in chromosome 19, or whose location in this complex is unknown. Here, by studying the family segregation of the KIR alleles 2DS3*001, *002 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 34 publications
5
54
0
Order By: Relevance
“…The reason for this is that without determining copy number or defining alleles, ascertainment of the gene arrangements on these haplotypes can be obscured by variation in KIR gene content of the partnering chromosome, even with pedigrees to track gene transmission . Six of the uncommon gene combinations (haplotypes 12, 13, 14, 15, 18, and 33) appeared to match recombinant haplotypes reported previously by us and others (Gomez-Lozano et al 2003, 2005Martin et al 2003;Ordonez et al 2008Ordonez et al , 2011Traherne et al 2010). Using published methods for detecting hybrid genes (e.g., 2DL5/3DP1 [3DP1*004], 2DS2/2DS3 [2DS2*005], and 2DL3/2DP1) and specific alleles associated with these recombinant haplotypes, we were able to Gene copy number varies from zero to three copies on a single haplotype.…”
Section: Many Kir Haplotypes Exhibit Novel Structural Variationmentioning
confidence: 49%
See 1 more Smart Citation
“…The reason for this is that without determining copy number or defining alleles, ascertainment of the gene arrangements on these haplotypes can be obscured by variation in KIR gene content of the partnering chromosome, even with pedigrees to track gene transmission . Six of the uncommon gene combinations (haplotypes 12, 13, 14, 15, 18, and 33) appeared to match recombinant haplotypes reported previously by us and others (Gomez-Lozano et al 2003, 2005Martin et al 2003;Ordonez et al 2008Ordonez et al , 2011Traherne et al 2010). Using published methods for detecting hybrid genes (e.g., 2DL5/3DP1 [3DP1*004], 2DS2/2DS3 [2DS2*005], and 2DL3/2DP1) and specific alleles associated with these recombinant haplotypes, we were able to Gene copy number varies from zero to three copies on a single haplotype.…”
Section: Many Kir Haplotypes Exhibit Novel Structural Variationmentioning
confidence: 49%
“…For example, the haplotype motif tA01 may have either form of 2DS4 (2DS4f or 2DS4v), and tB01 may have either variant of 2DS3S5 (2DS3 or 2DS5). T and C suffixes for 2DL5 (2DL5A or 2DL5B) and 2DS3S5 indicate the telomeric and centromeric versions of the genes, respectively (Gomez-Lozano et al 2002;Ordonez et al 2008;Pyo et al 2010). For simplicity, 2DS1 and 2DS4 are shown at the same site because they showed a mutually exclusive relationship.…”
Section: Disease Analyses Can Be Simplified But Current Kir Typing Imentioning
confidence: 99%
“…To rule out this possibility and, also, to map KIR2DS2*005 in the unusual haplotype, we studied its arrangement through analysis of the genes flanking KIR2DS2*005. Using a KIR-gene walking approach, 11 we found KIR2DS2*005 downstream of KIR3DL3, the normal arrangement of these two genes. On the contrary, we found that KIR2DS2 was followed not by KIR2DL2 as it happens in most haplotypes, but by the KIR2DP1 pseudogene, from which KIR2DS2 is normally separated by three KIR genes (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Genetic features of KIR2DS2*005 In a previous study on KIR-B haplotypes, we identified a healthy Caucasoid woman carrying KIR2DS2*005, 11 an uncommon allele with a hybrid primary structure. KIR-gene segregation in her sibling revealed that KIR2DS2*005 was inherited in a KIR haplotype that lacked a KIR2DL2 gene (Figure 1), whereas its central and telomeric regions were characteristic of B haplotypes (KIR 3DP1-2DL4-3DS1-2DL5A*001-2DS5-2DS1-3DL2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation